Peningkatan Produktivitas Karyawan PT. NBI melalui Pelatihan Microsoft Excel sebagai Strategi dalam Pengelolaan Data Perusahaan - Aulia, Lathifatul; Zakaria Bani Ikhtiyar; Agung Ginanjar; Arista Fitri Diana (Jurnal Atma Inovasia, 2024)
PT Nusantara Building Industries (NBI) is one of the national private companies located in Central Java Province which is engaged in the building materials industry in the form of symmetrical corrugated cement chrysotile fiber sheets. PT NBI tries to meet the needs of consumers according to demand and make various innovations in producing its products. Therefore, it is necessary to carry out a training to improve the soft skills of PT NBI employees in the form of Microsoft Excel training. Microsoft Excel is a software application used to carry out various activities, including data analysis, graph making, complex calculations, and various other tasks. Based on the purpose of implementing community service activities, namely increasing employee productivity. So that the implementation of this training is in accordance with the objectives, namely being able to assist PT NBI employees in finding effective ways to manage and analyze company data. In addition, it can increase understanding in the use of Microsoft Excel. The focus of Microsoft Excel training on the AND/OR function is used to perform logical evaluation of several conditions or criteria. This training is designed to introduce the use of AND/OR functions in the company. This method aims to increase the effectiveness and efficiency of work when encountering cases in several conditions or criteria. The evaluation results of the training implementation showed a good level of acceptance from PT NBI employees towards understanding and using the AND/OR formula. Keywords — Enterprise, Microsoft Excel, AND/OR Function, Data Analysis.